The Influence of Competence, Discipline, and Transformational Leadership on Performance with Job Satisfaction as an Intervening - Karmilah, Siti; Sugiono, Edi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
In the era of globalization, employee performance is one of the important factors that determine the success of an organization, including the National Food Agency. Optimal employee performance is needed to face challenges and meet increasingly complex demands in the food sector. The purpose of this study was to analyze the Influence of Competence, Work Discipline, and Transformational Leadership Style on Employee Performance at the National Food Agency with Job Satisfaction as an Intervening Variable. The research method used is quantitative descriptive with SmartPLS statistical analysis of 150 respondents. The results of the study indicate that 1) Competence, Work Discipline and Transformational Leadership Style directly affect job satisfaction; 2) Work Discipline and Job Satisfaction directly affect ASN Employee Performance; 3) Competence does not directly affect ASN employee performance; 4) Transformational Leadership Style directly affects ASN Employee Performance; 5) Competence, Work Discipline and Transformational Leadership Style directly affect ASN employee performance through job satisfaction.